INTERFERENSI NAHWU DALAM PENULISAN PIDATO BAHASA ARAB: STUDI KASUS PORSENI SE-KKMTS 01 GRESIK: INTERFERENCE OF NAHWU IN ARABIC SPEECH WRITING: A CASE STUDY OF PORSENI IN GRESIK - Nidaul Jannah; Asbarin; Muhammad Syihabul Ihsan Al Haqiqy; Mawadda Warahmah (Lisanul Arab: Journal of Arabic Learning and Teaching, 2025)
This study aims to analyze the errors  of the kitabah in the Arabic speech texts of PORSENI participants in KKMTs 01 Gresik based on the perspective of the nahwu rule. The background of this research departs from the importance of writing skills in Arabic, especially in the context of formal speeches that demand syntactic and morphological accuracy. Although Arabic language learning has been implemented in educational institutions, there are still various errors in sentence structure, i'rab, and the use of idhafi tarkib and number tarkib in the speech text of participants. This study uses a qualitative approach with the Error Analysis method. Data was collected through the documentation of participants' speech texts, which were then analyzed based on the nahwu rule to identify the types and factors that caused the error. The results of the study show that the most dominant mistakes are i'rab errors, the use of fi'il and dhamir, and the structure of tarkib that is not in accordance with the rules of the Arabic language. The main factors that caused this error included the participants' lack of understanding of syntactic rules, the influence of the mother tongue, and the lack of practice in compiling formal speech texts. As a recommendation, this study suggests the application of learning methods based on error analysis, increased writing and speaking practice in Arabic, and intensive mentoring for competition participants. It is hoped that this strategy can improve the language skills of participants and reduce errors in the use of nahwu rules.